Availability analysis of distillery plant using petri nets. Issue 10 (29th November 2018) - Bahl, Ankur; Sachdeva, Anish; Garg, Rajiv Kumar
Abstract : Purpose: The purpose of this paper is to prepare a methodology to evaluate availability analysis of distillery plant using Petri nets (PN). The effect of various failures, repair rate and availability of repair facilities on the system has been studied. Design/methodology/approach: The PN model of a system is developed to study the dynamic behavior of the system under various working conditions. Availability analysis of the plant is presented taking into consideration of failure and repair rates of their subsystems and has been carried out using Monte Carlo simulation. Findings: The bottle washing machine is the most critical machine from a maintenance point of view which has more compact on the system performance as compared to other machines. The availability analysis of distillery plant helps the management to adopt a suitable maintenance policy to improve upon plant production and plant availability. Originality/value: The application of this proposed PN-based approach is very useful in finding the most critical subsystem and its effect on the performance of the system in terms of availability and plant production. Further, the advantage of the PN approach is that dynamic behavior of the system under consideration is modeled with graphic representation of the system and given distribution can be associated with the subsystems for analysis. The superiority of this approach over others, such as network, fault tree and Markov analysis, is outlined in the paper.